2017
DOI: 10.3233/jpd-171088
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Alpha-Synuclein From Paraffin Embedded Autopsy Specimens in Parkinson’s Disease

Abstract: Background Parkinson disease (PD) is neurodegenerative disorder characterized by tremor, rigidity and bradykinesia and pathologically by the deposition of alpha-synuclein within different tissues. We, and others, have reported the detection of cutaneous alpha-synuclein in individuals with PD. Objective The goal of the present study was to detect alpha-synuclein deposition by immunohistochemical staining of skin samples in pathologically confirmed cases of PD. Methods Post-mortem skin biopsy samples from 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…85 The prevalence of alpha-synuclein pathology in the skin in patients with LBD is shown in Table 4. 30,33,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100] Subsequent biopsy studies revealed the frequent occurrence of alpha-synuclein pathology in the skin of patients with PD, DLB, and pure autonomic failure. [87][88][89][90][91][92][93][94][95][96][97][98][99][100] Doppler et al reported that alphasynuclein pathology was found in the skin in 16 of 31 patients with PD, and that the highest density of alpha-synuclein deposits was found in the back with 11 cases, while there were six cases in the proximal leg, four in the distal leg, and five in the finger, suggesting a decline in density from proximal to distal sites.…”
Section: Skinmentioning
confidence: 99%
“…85 The prevalence of alpha-synuclein pathology in the skin in patients with LBD is shown in Table 4. 30,33,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100] Subsequent biopsy studies revealed the frequent occurrence of alpha-synuclein pathology in the skin of patients with PD, DLB, and pure autonomic failure. [87][88][89][90][91][92][93][94][95][96][97][98][99][100] Doppler et al reported that alphasynuclein pathology was found in the skin in 16 of 31 patients with PD, and that the highest density of alpha-synuclein deposits was found in the back with 11 cases, while there were six cases in the proximal leg, four in the distal leg, and five in the finger, suggesting a decline in density from proximal to distal sites.…”
Section: Skinmentioning
confidence: 99%
“…The number of studies evaluating αSN deposition within cutaneous nerve fibers has increased in recent years. Most of these studies evaluating synuclein deposition in the dermal nerve fibers used a case–control design with clinically diagnosed cases, while only a few studies used tissue from cases verified by autopsy 13142021222324252627282930313940Table 1 summarizes the studies that used autopsy samples, while Table 2 summarizes the studies that used in vivo samples from clinically diagnosed subjects.…”
Section: Previous Studies Of αSn Deposition In Cutaneous Nerve Fibersmentioning
confidence: 99%
“…The methods used in the four postmortem studies were comparable in regard to tissue preparation, with the autopsy samples being fixed in formalin or formaldehyde solution (in 3.75% or 10% solution for more than 24 hours), embedded in paraffin, sectioned (at 5–6 µm), and stained 13143940. One major difference was the antibodies used: two studies selected antibodies against p-αSN, while the other two studies used antibodies against total αSN.…”
Section: Previous Studies Of αSn Deposition In Cutaneous Nerve Fibersmentioning
confidence: 99%
“…Immunohistochemical analysis of skin biopsies from PD patients and healthy controls, using an antibody against t‐α‐syn (Rodriguez‐Leyva et al ) reported increased α‐syn staining in PD patients compared to controls. In another recent study, analysis of post‐mortem skin biopsy samples from PD patients and controls for total α‐syn expression using immunohistochemistry (Gibbons et al ) revealed wider staining of α‐syn in both abdominal and scalp biopsies of PD patients compared to controls. A cross‐sectional study investigated whether pS129‐α‐syn in skin nerve fibres could serve as a useful biomarker for PD diagnosis, finding that pS129‐α‐syn was observed in all idiopathic PD patients, but not in PD patients assumed to not have α‐syn and controls (Donadio et al ).…”
Section: Detection Of α‐Syn In Peripheral Tissuesmentioning
confidence: 97%